Interpersonal Cognitive Distortions Among the Community-dwelling Elderly in Tehran, Iran - Zahra Kashaninia; Goharalsadat Sharifi; Naeime Seyedfatemi; Shima Haqqani (Iran University of Medical Sciences, 2022)
Background & Aims Interpersonal cognitive distortion (ICD) is one of the psychological problems in old age that causes a person not to have a correct and logical understanding of relations. Its continuation can lead to anxiety and depression. This study aims to determine the ICDs among the community-dwelling elderly in Tehran, Iran. Materials & Methods In this descriptive-correlational study, participants were 200 older people dwelling in the urban parks in Tehran, Iran who were selected using a cluster sampling method from December 2020 to October 2021. Data collection tools included a demographic form, abbreviated mental test score (AMTS), and interpersonal cognitive distortion scale (ICDS). The collected data were analyzed in SPSS software, version 16 software using descriptive statistics (Mean±SD, No. (%)) and inferential statistics (Pearson correlation test, independent t-test, analysis of variance). Results The mean total score of ICD was 52.53±8.29 out of 95, which indicates the moderate level of ICD among the elderly. In terms of the dimensions of ICDS, the unrealistic relationship expectations had the highest mean score (2.91±0.57), while the dimension of interpersonal rejection had the lowest score (2.64±0.52). There was a significant relationship between the age of the elderly and their ICD (P=0.03). Conclusion Considering the existence of a significant relationship between ageing and cognitive distortions, The nurses working in healthcare centers in Mashhad should take it into account in interventions for the elderly.